1994
DOI: 10.1080/00480169.1994.35797
|View full text |Cite
|
Sign up to set email alerts
|

Development of a diagnostic blood test for tuberculosis in alpacas (Lama paces)

Abstract: Vaccination of alpacas (Lama pacos) with heat-killed Mycobacterium bovis (BCG) in oil adjuvant produces an immune response that is able to be measured in vitro. Lymphocyte transformation was present 2 weeks after boosting while antibody as measured by the enzyme-linked immunosorbent assay was present 4-6 weeks after primary vaccination. Two vaccinated animals were positive to the intradermal skin test at the conclusion of the experiment and showed signs of systemic inflammation 72 hours after the skin test, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
1
5
1
Order By: Relevance
“…In cattle, haptoglobin is considered a major APP as immune‐stimulation can raise concentrations from undetectable levels to concentrations increased by up to 100‐fold . This appears to be in contrast to alpacas in this and another study in which concentrations of approximately 1 mg/mL occurred before experiments . Measureable increases in haptoglobin concentrations after low‐dose LPS challenge in the present study suggest that more pronounced haptoglobin changes can be expected in clinical practice, where bacterial infections are common.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…In cattle, haptoglobin is considered a major APP as immune‐stimulation can raise concentrations from undetectable levels to concentrations increased by up to 100‐fold . This appears to be in contrast to alpacas in this and another study in which concentrations of approximately 1 mg/mL occurred before experiments . Measureable increases in haptoglobin concentrations after low‐dose LPS challenge in the present study suggest that more pronounced haptoglobin changes can be expected in clinical practice, where bacterial infections are common.…”
Section: Discussioncontrasting
confidence: 62%
“…Previous reports on the use of haptoglobin assays in alpacas are sparse, but increased haptoglobin concentrations were observed in alpacas vaccinated with a Mycobacterium bovis vaccine . In that study, intradermal tuberculin skin testing resulted in increased serum haptoglobin concentrations of up to 0.44 mg/mL . The earliest significant increase in haptoglobin concentration was detected in TG‐alpacas at 36 hours, which is similar to cattle in which large increases are detected 2 days after inflammatory challenge .…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The comparative tuberculin skin test in the postaxillary site is the recommended diagnostic test in the UK and many other countries, although this test has not been fully validated and is technically more difficult to perform in camelids than in cattle. Some small studies have reported reasonable sensitivity and specificity for this test (Thoen and others 1988, Johnson and others 1989, Stevens and others 1998, Cousins and Florisson 2005); however, others have suggested that it has a low predictive value (Bleem and others 1993, Hesketh and others 1994).…”
Section: Figurementioning
confidence: 98%
“…26,47 In naturally infected Bactrian camels, ELISA and immunoelectrophoresis detected antibodies to multiple mycobacterial species, including M. bovis, which may explain why camelids show a high frequency of falsepositive tuberculin reactions. Routine screening is recommended as part of their regular health evaluation and may be required by regulatory agencies for interstate or international movement.…”
Section: Camelidsmentioning
confidence: 99%